New EU Industrial Policy – Principles, Problems, Opportunities - Spasova, Elena (Economy and Business Yearbook, 2022)
After being denounced as obsolete and ineffective in the last decades, the idea of European industrial policy is being revived. The newly created paradigm of the industrial policy at the EU level after 2009 is observed and analyzed in the context of contemporary technological changes and the role of EU in them; as well as the structure of intra-EU and extra-EU trade. The article discusses the possibility of building a strategic industrial policy at the EU level, considering the economic performance of the Community. The global context is also taken into account. Recommendations for modem industrial policy aimed at restoring economic growth and technological competitiveness are proposed.